Regulation of the Immune System Development by Glucocorticoids and Sex Hormones - Quatrini, Linda; Ricci, Biancamaria; Ciancaglini, Cecilia; Tumino, Nicola; Moretta, Lorenzo (Frontiers in Immunology, 2021)
Through the release of hormones, the neuro-endocrine system regulates the immune system function promoting adaptation of the organism to the external environment and to intrinsic physiological changes. Glucocorticoids (GCs) and sex hormones not only regulate immune responses, but also control the hematopoietic stem cell (HSC) differentiation and subsequent maturation of immune cell subsets. During the development of an organism, this regulation has long-term consequences. Indeed, the effects of GC exposure during the perinatal period become evident in the adulthood. Analogously, in the context of HSC transplantation (HSCT), the immune system development starts de novo from the donor HSCs. In this review, we summarize the effects of GCs and sex hormones on the regulation of HSC, as well as of adaptive and innate immune cells. Moreover, we discuss the short and long-term implications on hematopoiesis of sex steroid ablation and synthetic GC administration upon HSCT.